2005
DOI: 10.1007/s10350-005-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Histology With Anorectal Function Following Stapled Hemorrhoidectomy

Abstract: Some smooth muscle will invariably be excised in stapled hemorrhoidectomy but the amount of smooth muscle removed did not significantly affect the continence score, quality of life, or mean anal resting pressure after stapled hemorrhoidectomy. It remains a safe and preferred procedure for the treatment of hemorrhoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 8 publications
(10 reference statements)
1
20
0
2
Order By: Relevance
“…Presence of malpighian tissue may be a less precise indicator of staple line height as its superior limit varies above the dentate line [17], explaining why this criterion was not related to new onset incontinence symptoms in our patients. Neither was the presence of smooth muscle fibers, as they probably issue from the rectal muscular wall above the internal sphincter [18,19]. The other factors associated with incontinence (surgeon, doughnut <12 mm, congestive external hemorrhoids) were probably linked: doughnut height was lower when resection was 332 performed near the dentate line, due to a lesser submucosa elasticity at this level, the purse string was performed lower when external hemorrhoids were present in an attempt to reduce them, and one of the three surgeons voluntarily made low resections involving most of the hemorrhoidal tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Presence of malpighian tissue may be a less precise indicator of staple line height as its superior limit varies above the dentate line [17], explaining why this criterion was not related to new onset incontinence symptoms in our patients. Neither was the presence of smooth muscle fibers, as they probably issue from the rectal muscular wall above the internal sphincter [18,19]. The other factors associated with incontinence (surgeon, doughnut <12 mm, congestive external hemorrhoids) were probably linked: doughnut height was lower when resection was 332 performed near the dentate line, due to a lesser submucosa elasticity at this level, the purse string was performed lower when external hemorrhoids were present in an attempt to reduce them, and one of the three surgeons voluntarily made low resections involving most of the hemorrhoidal tissue.…”
Section: Discussionmentioning
confidence: 97%
“…A too-deep purse-string with incorporation of muscle cells may be related to rare but severe complications such as rectal perforation and rectovaginal fistula [8], and has been correlated with postoperative pain [9], and a trend towards a worse quality of life [10]. Removal of only anorectal mucosa without smooth muscle is difficult even in experienced hands and may be achieved in only 6% patients [10].…”
Section: Discussionmentioning
confidence: 98%
“…Kam et al [28] showed that some smooth muscle is invariably excised in SHP but the amount of smooth muscle removed did not significantly affect the continence score, quality of life, or mean anal resting pressure after SHP. With a decrease in rectal compliance, volume thresholds for sensations decrease causing rectal urgency and/or increased stool frequency [29].…”
Section: Fecal Urgency and Incontinencementioning
confidence: 99%